Pancreatic serous cystadenocarcinoma with invasive growth into the colon and spleen - Cho, Wontae (The Korean Surgical Society, 2011)
Serous cystic neoplasms of the pancreas are almost always benign lesions. However, there are some case reports of malignant serous neoplasms of the pancreas. It is very difficult to distinguish malignant and benign tumors. Indeed, only clinicopathologic findings of locoregional invasion and metastasis represent a malignancy. We report a serous cystadenocarcinoma of the pancreas that was initially considered to be colon cancer. Post-operatively, the tumor was confirmed to be a malignant serous cystic tumor of the pancreas. One year later, the patient remains disease-free.